Actin regulation in the malaria parasite - Sattler, Julia M.; Ganter, Markus; Hliscs, Marion; Matuschewski, Kai; Schüler, Herwig (European journal of cell biology, 2011)
Many intracellular pathogens hijack host cell actin or its regulators for cell-to-cell spreading. In marked contrast, apicomplexan parasites, obligate intracellular, single cell eukaryotes that are phylogenetically older than the last common ancestor of animals and plants, employ their own actin cytoskeleton for active motility through tissues and invasion of host cells. A hallmark of actin-based motility of the malaria parasite is a minimal set of proteins that potentially regulate microfilament dynamics. An intriguing feature of the Plasmodium motor machinery is the virtual absence of elongated filamentous actin in vivo. Despite this unusual actin regulation sporozoites, the transmission stages that are injected into the mammalian host by Anopheles mosquitoes, display fast (1-3μm/s) extracellular motility. Experimental genetics and analysis of recombinant proteins have recently contributed to clarify some of the cellular roles of apicomplexan actin monomer- and filament-binding proteins in parasite life cycle progression. These studies established that the malaria parasite employs multiple proteins that bind actin to form pools of readily polymerizable monomers, a prerequisite for fast formation of actin polymers. The motile extracellular stages of Plasmodium parasites are an excellent in vivo model system for functional characterization of actin regulation in single cell eukaryotes.
Gesehen am 06.10.2022